HSV1 glycoprotein D utilizes an LY6-like binding domain to inhibit alpha7 nicotinic receptors - Sabina Yeasmin; Kavita Sharma; Christopher Nicolet; Laura DeCristofano; Yeganeh Ataian; Arina Ranjit; Ali Aghazadeh-Habashi; Dong Xu; Marvin Schulte (npj Viruses)
Abstract Herpes virus1(HSV1) is a neurotropic virus that has been linked to Alzheimer’s disease. An In-silico structural homology search using α -Bgtx, identified structural homology between HSV1 gD and the nicotinic receptor neurotoxin α-Bgtx. SPR binding studies using acetylcholine binding protein from Lymnaea stagnalis, and functional two electrode voltage clamp studies of α7 nAChRs demonstrate the ability of HSV1 to interact directly with nAChRs. Molecular docking studies support the binding of a neurotoxin-like binding loop in HSV1 to a binding site similar to the neurotoxin binding domain. Interaction of HSV1 with nAChRs provides novel insights into a potential mechanism of action of HSV and its potential role in Alzheimer’s disease.